(untitled) (Revista Inclusiones, 2020)
The paper describes the relationship between the economy in the traditional sense, the digital economy and law in the context of modern technology of the beginning of the 21st century and the Fourth Industrial Revolution. As long as law takes roots in the economy, it is at the current stage inevitably subject to digitalisation. The text contains brief descriptions of the above-mentioned types of economy and provides examples of the digitalisation of the legal field. Alongside, some problems are outlined that have to be addressed both at the national legislative level and under the framework of international law. The general philosophical approach of this legal study refers to the positivist methodology focused on analysing specific facts and deriving patterns of objective reality. It makes the basis for employing certain specific and general methods. The study concludes that the legal system integrates numerous components such as legislation, legal practice, legal theory as a science and legal culture. All these components of the legal system in modern Russia will be transformed. Still, it will primarily affect the biggest blocks of the legal system, that is, the system of law and the legislative system.